Build Windows 8 apps with Microsoft Visual C++ step by step - Regnicoli, Luca (Step by step (Redmond, Wash.), 2013)
Your hands-on, step-by-step guide to building Windows 8 apps with Microsoft Visual C++ Teach yourself how to build Windows 8 applications using the Visual C++ language--one step at a time. Ideal for those with intermediate to advanced C++ development skills, this tutorial provides practical, learn-by-doing exercises for creating apps that can adapt to different screen sizes--including desktop and laptop computers, tablets, and slates. Discover how to: Build apps using Windows 8 design guidelines Explore the Windows 8 application architecture Apply tools and libraries from Microsoft Visual Studio and the Windows 8 SDK Use XAML to create touch-optimized user interfaces Create apps that make use of device sensors Manage the Windows 8 application lifecycle Prepare your app for the Windows Store.